Chemical prosperity of various chemical gypsums from viewpoint of particle morphology. (8th April 2015) - Tafu, M; Toshima, T; Manaka, A; Chohji, T; Irie, M
Abstract: Dissolution rate of various chemical gypsums in the water was investigated by using batch experiment. The rate of the dissolution of the gypsum had good agreement for explanation of dissolution of plate particle. The rate constants of the experimental formula were different with particle morphology of the gypsums. When morphology of the particle was sheet-liked, the dissolution rate was 10 timed large than it of block-shaped particle. From result of observation of dissolution phenomena of the in the water, it was find that dissolution of the gypsum was preceded on long axis. From these results, particle morphology is seems to be important parameter for using chemical gypsums.